Vehicle speed detection using frame differencing for smart surveillance system - Hasliza, A. Rahim@Samsuddin; Usman Ullah, Sheikh, Dr.; R. Badlishah, Ahmad, Prof. Madya Dr.; Aini Syuhada, Md Zain; Wan Nur Suryani Firuz, Wan Ariffin (Institute of Electrical and Electronics of Engineering (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/